2017
DOI: 10.1139/cjfas-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of phenology in a salmonid population: a potential adaptive response to climate change

Abstract: Accumulating evidence has indicated that many fish populations are responding to climate change through shifts in migration time, but genetic data identifying the role of evolution in these shifts are rare. One of the first demonstrations of evolution of migration time was produced by monitoring allozyme alleles that were experimentally manipulated to genetically mark late-migrating pink salmon (Oncorhynchus gorbuscha). Here, we extend that research by using observations of the marker alleles in fry to demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Similar responses to climate change have already been observed in both lineages with changes to migration timing thought to better match new environmental conditions. Kovach et al (2013) observed earlier migration timing in both lineages, and evidence for the genetic basis of the change in the odd-year lineage is accumulating (Kovach et al 2012, Manhard et al 2017).…”
Section: Allochrony and Pink Salmonmentioning
confidence: 95%
“…Similar responses to climate change have already been observed in both lineages with changes to migration timing thought to better match new environmental conditions. Kovach et al (2013) observed earlier migration timing in both lineages, and evidence for the genetic basis of the change in the odd-year lineage is accumulating (Kovach et al 2012, Manhard et al 2017).…”
Section: Allochrony and Pink Salmonmentioning
confidence: 95%
“…It is well established that adult salmonid migration timing and spawn timing are genetically heritable over generations [ 17 , 18 ] and that these traits reflect historical adaptation to river discharge and temperature patterns [ 19 , 20 ]. There is also accumulating evidence that recent phenological shifts in many salmonid populations have occurred in response to climate-driven warming and have been accompanied by genetic changes [ 21 23 ]. What is much less clear is whether population-level adaptation can keep pace with climate change, and this is currently a central question in salmonid conservation and management.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the biological limit of 4 kJ/g to sustain biological function under prevailing temperatures could not explain the end of the observed spawning migration. Other factors such as subsequent selection pressures and evolutionary feed‐backs resulting from the poor survival of eggs and fry as a consequence of late spawning are likely mechanisms that could explain the end of the spawning migration (Brannon, ; Manhard, Joyce, & Gharrett, ; Rand et al., ). The inability for energy use to explain the end of the observed spawning migration was not an unexpected result.…”
Section: Discussionmentioning
confidence: 99%